Evaluation of 'The Father Effect' Media Campaign to Increase Awareness of, and Participation in, an Online Father-Inclusive Parenting Program. Issue 12 (15th October 2019) - Tully, Lucy A.; Piotrowska, Patrycja J.; Collins, Daniel A. J.; Frick, Paul J.; Anderson, Vicki; Moul, Caroline; Lenroot, Rhoshel K.; Kimonis, Eva R.; Hawes, David; Dadds, Mark R.
ABSTRACT: There is substantial evidence that parenting programs are effective in improving parenting and child mental health outcomes. While there is increasing focus on delivering parenting interventions online to increase their reach and dissemination, fathers are underrepresented in all formats of parenting programs. However, research suggests that father participation is important for intervention effectiveness. This study evaluated the effectiveness of a media campaign for increasing awareness of, and participation in, an online father-inclusive parenting program called 'ParentWorks'. An 8-week campaign was conducted in Australia via social media channels, digital display advertising, digital television, and radio. To assess the impact of the campaign, data were obtained from caregivers registering for ParentWorks during the campaign period ( n  = 848) and an 8-week comparison period that occurred 3 months later ( n  = 254). Additionally, a nationally representative sample of 2021 caregivers of children aged 2–16 years completed an online survey. Survey questions asked about exposure to the campaign, registration for participation in ParentWorks, and knowledge of the importance of father participation in parenting programs. Three times as many caregivers registered during the 8-week media campaign compared to the comparison period, and a significantly greater proportion of male caregivers registered in the campaign versus the comparison period. The online survey found that 11% of caregivers reported exposure to the campaign, and significantly more fathers than mothers reported exposure. Results showed that those who were exposed to the campaign were significantly more likely to endorse the importance of father participation in parenting programs, than those not exposed to the campaign. The findings indicate that media campaigns appear to be an effective method of increasing awareness of online parenting programs and enhancing rates of father involvement.